HIV-infected presumptive tuberculosis patients without tuberculosis: How many are eligible for antiretroviral therapy in Karnataka, India?. Issue 1 (March 2017) - Kumar, Ajay M.V.; Singarajipura, Anil; Naik, Balaji; Guddemane, Deepak K.; Patel, Yogesh; Shastri, Suresh; Kumar, Sunil; Deshmukh, Rajesh; Rewari, B.B.; Harries, Anthony David
Abstract: For certain subgroups within people living with the human immunodeficiency virus (HIV) [active tuberculosis (TB), pregnant women, children <5 years old, and serodiscordant couples], the World Health Organization recommends antiretroviral therapy (ART) irrespective of CD4 count. Another subgroup which has received increased attention is "HIV-infected presumptive TB patients without TB". In this study, we assess the proportion of HIV-infected presumptive TB patients eligible for ART in Karnataka State (population 60 million), India. This was a cross-sectional analysis of data of HIV-infected presumptive TB patients diagnosed in May 2015 abstracted from national TB and HIV program records. Of 42, 585 presumptive TB patients, 28, 964 (68%) were tested for HIV and 2262 (8%) were HIV positive. Of the latter, 377 (17%) had active TB. Of 1885 "presumptive TB patients without active TB", 1100 (58%) were already receiving ART. Of the remaining 785 who were not receiving ART, 617 (79%) were assessed for ART eligibility and of those, 548 (89%) were eligible for ART. About 90% of "HIV-infected presumptive TB patients without TB" were eligible for ART. This evidence supports a public health approach of starting all "HIV-infected presumptive TB patients without TB" on ART irrespective of CD4 count in line with global thinking about 'test and treat'.